ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. PELINDO II CABANG BENGKULU. - Syofian Syofian (Universitas Prof. Dr. Hazairin SH, 2018)
This research was conducted to find out and measure the variable quality of service (tangible, reliability, responsiveness, assurance, emphaty) significantly influence customer satisfaction PT. Pelindo II Cab. Bengkulu. The method of data collection is carried out by observation and questionnaire methods. The results showed the dimensions of Tangible service quality (X1), Reability (X2), Responsiveness (X3), Assurance (X4) and Emphaty (X5), together had a positive effect. Regression equation Y = 4.721 + 0.207 X1 + 0.222 X2 + 0.182 X3 + 0.350 X4 - 0.394 X5. F test amounted to 27,221 while F table 2,31, means F-count> F-table (27,221> 2,31). The results show the quality of tangible, reability, responsiveness, assurance, and empathy services together have a positive and significant effect on the variable customer satisfaction. The t test is known to show the Tangibles Variable t count of 3.384. This value is greater than t table (3,384> 1,986). Reliability Variables t count at 3.058 this value is greater than t table (3.058> 1.986). The Responsiveness variable t counts for 1,992 this value is greater than t table (1992> 1,986). Variable Assurance t count at 6,576, this value is greater than t table (6,576> 1,986). Empathy variable has a value of t count of -7,259. This value is greater than t table (-7.259 <1,986)